Implementasi Teori Work Adjustment dalam Meningkatkan Kematangan Karir Siswa SMK - Pratiwi, Hanifah (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Vocational high schools aim to prepare students to be ready to work in the field. Vocational high school (SMK) as one of the high school levels that we prepare to go directly into the world of work. In this case, the career maturity of vocational students needs to be improved. Therefore, the role of work adjustment theory is one theory that is suitable for use by Bk teachers to help improve career information for vocational students in order to improve the careers of vocational students. This research uses qualitative research using field research. Field research is a research conducted in a structured manner by lifting data that already exists in the field. In this study, the related subject is SMK students who will later work after completing their education.